Creativity-enhancing work environments: eventisation through an inspiring work atmosphere in temporary proximity = Kreativitätsfördernde Arbeitsorte : Eventisierung durch eine inspirierende Arbeitsatmosphäre und temporäre Nähe - Wagner, Madeleine; Growe, Anna (Raumforschung und Raumordnung, 2020)
The objective of this paper is to understand how work processes and the quality of physical places support creative knowledge generation. The creation of knowledge is linked to both social space and physical place, and is influenced by steady socio-spatial dynamics. In workplaces, the space-time dynamics of knowledge creation coincide with the physical characteristics of place. On the basis of qualitative interviews with Design thinking workshop facilitators, as well as participants, the influence of three types of creative support (psychosocial, inspirational and functional) is linked to the elements of place, people and process in this specific innovation method. This paper discusses in which ways place, people and process contribute to creating a creativity-enhancing workspace and inspiring atmosphere in temporary spatial proximity. Eventisation of the innovation process, and interaction in temporary spatial proximity, are important prerequisites for keeping knowledge creation exciting.